Enchanted again - Owens, Robin D. (Don Mills, Luna, 2012)
"Magic has a price--and for Amber Sarga it's days and years off her life. Each curse she breaks ages her--and the bigger the curse the bigger the cost, and not only to her. That's why she hides away and has vowed not to get involved again-- That's why she hates looking in a mirror. And then an ill-fated stranger arrives. Rafe Davail doesn't believe in curses--not even knowing that in his family every first son dies young. Amber offers guidance but she won't break the curse. Still, as she grows closer to Rafe and discovers the secrets of their pasts, she wonders if for this time, this man, she should risk it all"--P. [4] of cover.
Keywords: Blessing and cursing -- Fiction; Magic -- Fiction; Paranormal fiction